Kualitas Kefir Kombinasi Susu Kacang Tunggak dan Susu Skim dengan Variasi Jenis Gula dan Lama Fermentasi - Fransiska Fransiska; Titik Suryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the quality (total acid content and organoleptic properties) of kefir combined with cowpea milk and skim milk with variations in sugar and fermentation time. The research used experimental methods and a completely randomized design (CRD) with two factors. Factor I is variations in the type of sugar (G), granulated sugar, and ant sugar. Factor II is the variation in fermentation time (L) between 36 hours and 48 hours. The results of the research showed that the best total acid content of kefir combined with cowpea milk and skim milk was 0.96%, pH 3.5, in the G1L1 treatment (granulated sugar + 36-hour fermentation time). The best organoleptic quality of kefir was in the G1L1 treatment (granulated sugar + fermentation time of 36 hours), with a pleasant aroma, sour taste, less viscousness, and a white color. Keywords: Cowpea, Kefir, Organoleptic, Skim Milk, Total Acid